Teaching Pediatric Palliative Care Communication Skills to Fourth-Year Medical Students Through Role-Play - Brittany Cowfer; Caitlin McGrath; Amy Trowbridge (Association of American Medical Colleges, 2020)
Introduction Despite growing recognition of pediatric palliative care's importance, training in palliative care communication remains a gap in medical education. Graduating medical students frequently feel unprepared to initiate or facilitate goals of care conversations with their patients, particularly in pediatrics. Methods We created a 3-hour session featuring an introductory lecture on pediatric palliative care, communication drills on responding to emotion, and small-group case-based discussions utilizing role-play, targeting fourth-year medical students as the primary learners. Senior residents were also given the opportunity to develop skills by role-playing the patient parent and cofacilitating case discussions alongside palliative care faculty. Students evaluated session utility and their own confidence through pre- and postsession surveys using a 5-point Likert scale (1 = strongly disagree, 5 = strongly agree). Results Twenty-six students were included in the analysis over 3 years. All agreed that the session was useful (M = 4.9). Students showed significant improvement in confidence in explaining pediatric palliative care (presession M = 3.2, postsession M = 4.1, p < .001), understanding the family experience (presession M = 2.7, postsession M = 4.1, p < .001), and eliciting goals and values from families whose children face serious illnesses (presession M = 3.1, postsession M = 4.1, p < .001). Pediatric resident cofacilitators also felt the session benefited their own teaching and communication skills. Discussion This 3-hour interactive session on pediatric palliative care utilizing communication drills and role-play was effective in improving fourth-year medical students' confidence in communicating with families of children facing life-threatening illnesses.